Answer:
the answer is 7/12 Hopefully this helps!
Answer:
The answer is
Step-by-step explanation:
we have
Solve for x
Divide by both sides
Square root both sides
-4(s)²+t³÷5
Answer:
Bryan needs 9 cups more.
Step-by-step explanation:
Bryan is cooking cupcakes for a bake sale at his club. The recipe calls for 12 cups of flour.
Number of cups of flour, he already has = 3
Lets say he needs x cups more.
So, equation forms =
=>
x = 9
Hence, Bryan needs 9 cups more.
Answer:
9 cups
Step-by-step explanation:
12-3 = 9
segment ZY is the radius of circle Y. Points W, X, C, Y, and
Z are all on line segment WZ.
What is the area of circle C, which passes though points W
and Z?
X
O 81 T units?
10
O 164 TT units?
O 324 units?
O 1296 units
Mark this and retum
Save and Exit
Next
Submit
ch
The area of the given Circle C is; 324π
From the attached diagram, we see that;
WX is the radius of circle X and is equal to 8 units
Similarly, ZY is radius of circle Y and is equal to 10 units.
Thus, diameter of circle X = 8 * 2 = 16 units
Diameter of circle Y = 10 * 2 = 20 units
Thus;
Diameter of circle C = 20 + 16 = 36 units
Area of Circle C = π * 36²/4
Area of Circle C = 324π
Read more about Area of circle at; brainly.com/question/15673093
Answer:
I think the answer is C. 324 but i'm not sure. lemme know if i'm wrong and what the correct answer is
Step-by-step explanation:
Answer:
Step-by-step explanation:
C (106)
g(x)=f(x)*h(x) ⇒g'(x)=f'(x)*h(x)+f(x)*h'(x) ⇒ g'(3)=f'(3)*h(3)+f(3)*h'(3)⇒ g'(3)=(8*2)+(6*15)= 16+90=106
The equation of the composite function is f(h(x)) = 2x-4.
Function composition is an operation ∘ that takes two functions f and g, and produces a function h = g ∘ f such that h(x) = g. In this operation, the functiong is applied to the result of applying the function f to x.
Here, f(x) = x - 7
h(x) = 2x + 3
Now, f(h(x)) = f ( 2x + 3)
= (2x+3)-7
= 2x + 3 -7
= 2x - 4
Thus, the equation of the composite function is f(h(x)) = 2x-4.
Learn more about Composite Function from:
#SPJ2
Answer:
Step-by-step explanation:
Write the rule for h(f(x)).
h(f(x)) = 2x - 11
Write the rule for f(h(x)).
f(h(x)) = 2x - 4